Comparison of Receptive Verbal Abilities Assessed Using the KBIT-2 and BPVS3 in Adults With Down Syndrome - Startin, Carla M.; Hamburg, Sarah; Strydom, Andre; , LonDownS Consortium (Frontiers in Psychology, 2019)
Down syndrome (DS) is the most common genetic cause of intellectual disability. There is, however, considerable variation in cognitive abilities between those with DS, with some individuals scoring at floor on some tests, particularly for age-standardised outcomes. This variation and these floor effects can pose a problem for comparing and combining study populations when different standardised measures have been used to assess individuals’ cognitive abilities, for example combining results across studies to investigate genetic or other factors associated with cognitive abilities. To facilitate this comparison and combination of study populations assessed using different tests of verbal abilities, we administered two commonly used standardised tests of receptive language, the Kaufmann Brief Intelligence Test 2 (KBIT-2) verbal scale and the British Picture Vocabulary Scale 3 (BPVS3) to 34 adults with DS (age range 19–59) to investigate relationships between outcomes for these two tests. We found a very strong correlation between raw scores for the KBIT-2 verbal scale and the BPVS3, and determined equations to convert between scores for the two tests. Intraclass correlations between the two scales for age-equivalents and calculated z scores relative to population norms were also strong, though scores for both outcomes were significantly higher for the KBIT-2 verbal scale compared to the BPVS3. This deviation in scores between the two tests was greater as z scores decreased for both tests (i.e., for lower scoring individuals), with no such relationship observed for age-equivalents. These results indicate the conversion of raw scores between the KBIT-2 verbal scale and the BPVS3 may be a more valid method for the comparison or combination of study samples with DS compared to the use of standardised scores. Such comparisons or combinations will aid our understanding of cognitive variations and factors associated with these variations within the population with DS.